Purification of papain from fresh latex of Carica papaya - Monti, Rubens [UNESP]; Basilio, Carmelita A. [UNESP]; Trevisan, Henrique C. [UNESP]; Contiero, Jonas [UNESP] (Brazilian Archives of Biology and Technology, 2000)
No presente trabalho apresenta-se um método de cristalização da papaína oriunda do látex fresco de mamão, o qual apresenta uma alta produtividade em relação aos métodos previamente descritos. A metodologia aqui descrita não envolve o uso de reagentes sulfidrílicos, a papaína foi obtida de forma praticamente pura, apresentando uma simples banda quando submetida a eletroforese, e com propriedades idênticas àquelas obtidas por outros métodos. A atividade específica foi determinada utilizando Z-gly-pNP e BAEE como substrato. A papaína obtida por essa metodologia, sem uso de substâncias tais como cisteína e ditiotreitol, apresenta-se na forma de um complexo com inibidores naturais, os quais podem ser removidos por diálise.

In the present study we wish to report a method of crystallizing papain from fresh papaya latex which gave higher yields than previously reported. This method does not involve the use of sulphydryl reagents. The papain thus obtained is practically pure and shows a single band when submitted to electrophoresis on polyacrylamide gel, and is identical to the papain obtained by other methods. In routine enzymatic assays, specific activity was measured using Z-gly-pNP and BAEE as substrates. Papain crystallized by this method, without the use of high concentrations of salts or thiol-containing substances such as cysteine and dithiothreitol, is obtained in the form of a complex with natural inhibitors existent in latex which can be removed by dialysis.
Keywords: Papain; Carica papaya; cysteine proteinase; proteolytic enzymes; purification of papain